Membangun Kembali Pemerintahan Pasca Pandemi COVID-19; Studi Pada Kapasitas Manajer Publik Untuk Kolaborasi - Taufik Taufik; Budi Setiyono; Retno Sunu Astuti; Kismartini (Jurnal Transformative, 2022)
The post-pandemic government is faced with the challenge of reorganizing the sectors affected by COVID-19. Cross-sectoral collaboration is one approach to this arrangement. This study aims to analyze the skills of public managers that can encourage government organizations to collaborate. This study uses a systematic review. Research stages: first identify studies using sources from several publishers, such as science direct, scopus, and emerald insight. Second, limiting the search in several fields of science, namely social science, management, political science, public administration, multidisciplinary, and health related to the handling of COVID-19. Third, conduct an assessment of the relevance and quality of the research objectives. Fourth, extracting data by categorizing, and Fifth, synthesizing data. There are five skills that must be possessed by public managers to collaborate across sectors, namely: program design skills or partnership projects; risk analysis skills, communication skills in this case able to negotiate well with stakeholders; skills to create public accountability, and fifth, skills to monitor and evaluate partnership programs. These skills must be possessed by public managers to achieve success in partnership or collaboration programs after the COVID-19 pandemic. So that efforts to rebuild sectors affected by COVID-19 can run effectively and efficiently through collaboration mechanisms.